The impact of Bolsa Família on schooling: Girls’ advantage increases and older children gain - de Brauw, Alan; Gilligan, Daniel O.; Hoddinott, John F.; Roy, Shalini (International Food Policy Research Institute, 2014)
We estimate the impact of Bolsa Família on a range of education outcomes, including school participation, grade progression, grade repetition, and dropout rates. Using a large-sample household panel survey from 2005–2009 collected for this evaluation, we develop a statistically balanced comparison group of eligible nonparticipant households and estimate impacts using propensity-score-weighted regression. We estimate that Bolsa Família increased average school participation among all children age 6 to 17 years by (a weakly significant) 4.5 percent. It had no effect on grade promotion, on average. However, within the subsample of girls, Bolsa Família caused substantial improvements in schooling outcomes, including significant increases in school participation (8.2 percent) and rates of grade progression (10.4 percent). We show that the gains in girls’ schooling do not derive from catch-up effects, but rather increase girls’ existing advantage in schooling attainment. In general, impacts are larger among older children, in rural areas, and in the Northeast.